Malawi's Infrastructure : A Continental Perspective - Foster, Vivien (World Bank, Washington, DC, 2017)
Infrastructure contributed 1.2 percentage points to the annual per capita growth of Malawi's gross domestic product (GDP) over the past decade, thanks mainly to the revolution in information and communication technology (ICT). Raising the country's infrastructure endowment to that of the region's middle-income countries could further boost annual growth by 3.5 percentage points per capita. Today, Malawi's basic infrastructure indicators look relatively good when compared with other low-income countries in Africa, although the performance of that infrastructure could be significantly improved. Malawi is one of the few African countries to have already reached the Millennium Development Goals (MDGs) for water, almost a decade ahead of the target. The private sector has made Global Management System (GSM) telephone signals widely available without public subsidy. A substantial road investment program has raised the average condition of the country's road network, and a foundation for institutional reform has been laid in the ICT, power, and road transport sectors. Even if those inefficiencies could be eliminated, Malawi will still face an infrastructure funding gap of almost $300 million a year. This could be lessened to $100 million by engaging in regional trade of electricity, using lower-cost supply modalities in water supply and sanitation, and adopting appropriate technologies for road sector development. As long as efficiency gains are captured and spending sustained at the levels of the recent past, the country's infrastructure targets could be reached within 16 years.